Cell-cell contact mediated signalling — no fear of contact - Schmidmaier, R.; Baumann, P.; Meinhardt, G. (Experimental Oncology, 2006)
Cancer research with sole focus on the cancer cell and possibly growth factors cannot faithfully reproduce the environmental interaction, such as adhesion of tumor cells to e.g. stromal cells, which may determine the response of these tumors to therapy. Methodologically cell adhesion studies are often difficult since complete but careful detachment is the prerequisite for most signal transduction assays. We describe for the first time an alternative method for the co-incubation of multiple myeloma cells on long term primary bone marrow stromal cultures using the bone marrow stromal cell line HS-5. The methods are precisely described, advantages and disadvantages are discussed, and troubleshooting advises are given. Исследования роста опухолевых клеток in vitro не отражают многих факторов (взаимодействие клеток с окружающей
средой, их адгезию к клеткам стромы), которые в свою очередь могут определять чувствительность опухоли к терапии.
Методологически изучение клеточной адгезии часто бывает затруднено, так как разделение клеток является основой
большинства методик по изучению передачи сигнала. Впервые описан альтернативный метод ко-культивирования клеток
множественной миеломы с клетками стромы линии HS-5, полученных из клеток костного мозга. Приведено подробное
описание, преимущества и недостатки этого метода с детальными техническими рекомендациями.